Karakteristik Tanah Gambut Yang Distabilisasi Terhadap Pebakaran - Z, Harist Febrie R; Muhardi, Muhardi; Wibisono, Gunawan (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Peat is a soft organic soil formed from the decomposition of plants caused by several factors. The largest peatland area in Indonesia located in Sumatra island. And 60,08% orapproximately 3.867.413 hectares of peatlands of Sumatra island located in Riau Province (Agency for Agricultural Research and Development of the Ministry of Agriculture, 2011). In the dry season on peatlands in Riau frequent fires. One among the method to reduce the risk of peat fires are compaction and stabilization. A stabilizing agent selected is limestone (CaCO3) and Porland Composite Cement(PCC). The purpose of this study to determine the optimum composition lime and cement to the stabilization of burning peat. Optimum moisture content was taken 100% based on Hadijah(2006) in Octriyana (2010). In UCS test, the highest percentage increase occured in variations Peat+5%CaCO3+15%PCC is equal to 59,44% from the value of q¬u pure peat soils. In CBR test, the highest percentage valueobtained in variation Peat+5%CaCO3+15%PCC is equal to 100,17% of CBR pure peat. While in burning process, peat with additive has a burning point and ash point more longerthan pure peat. With the additon of lime(CaCO3) and PCC cement, it can slow combustion process.Keywords: Peat Soils, PCC Cement, CaCO3,CBR, UCS,Burning Point, Ash Point